A Ti-MOF Decorated With a Pt Nanoparticle Cocatalyst for Efficient Photocatalytic H2 Evolution: A Theoretical Study - Zhong, Yeshuang; Wang, Ruihan; Wang, Xin; Lin, Zhien; Jiang, Gang; Yang, Mingli; Xu, Dingguo (Frontiers in Chemistry, 2020)
Pt Nanoparticles (NPs) are often used as cocatalysts to enhance the photocatalytic hydrogen production catalyzed by the metal organic framework (MOF) materials. The catalytic efficiency of many Pt/MOF systems can be greatly improved when Pt Nanoparticles used as cocatalysts. In this work, the Pt/20%-MIL-125-(SCH3)2 was chosen as the template material to understand the functional role of Pt metal cocatalyst in the catalytic process. Experimentally, the catalytic activity of Pt/20%-MIL-125-(SCH3)2 is more than 100 times that of the system without helping of Pt nanoparticles. Firstly, we proposed a searching algorithm, which is based on combined Monte Carlo (MC) method and principal component analysis (PCA) algorithm, to find that the most probable adsorption site of Pt13 nano-cluster loaded on the (001) surface of 20%-MIL-125-(SCH3)2. Next, by using density functional theory (DFT) and time-dependent density functional theory (TDDFT) methods, we revealed that the accumulation of some positive charges on Pt13 cluster and proton adsorbed on the Pt13 cluster, which can promote the separation of photogenerated electrons and holes, thus improving the photocatalytic efficiency. This work not only provides a method to obtain the adsorption configuration of metal clusters on various MOFs, but also provides a new insight into increasing photocatalytic efficiency for H2 production in Pt/MOF systems.systems.